SECTIONAL MANDIBULAR COMPLETE DENTURE FOR A TOTAL MAXILLECTOMY PATIENT WITH TRISMUS: A CLINICAL REPORT - Tamer ÇELAKIL; Azize DEMIR; Haluk KESKIN (Istanbul University, 2017)
This report presents the case of a 60-year-old male patient with trismus induced by radiotherapy and fabrication of a sectional mandibular complete denture to allow the insertion of the denture into the mouth. A mandibular sectional denture was designed in two pieces with a locking mechanism by using mini anchor and ball abutment housing with cap. Patients who have undergone maxillectomy often have constricted mouth openings, as a result of surgical intervention and radiotherapy, and complain of an inability to insert or remove dentures. A new approach is vital for sectional dentures because existing sectional denture fabrication techniques cannot meet the ongoing needs of trismus patients. The mini anchor system with ball abutment housing has better mechanical retention in acrylic resin and can provide favorable stabilization during masticatory function; thus, additional framework is not required for assisting in stabilization and retention.